Essays on Employee Ownership - Benjamin Faigen (Copenhagen Business School (CBS), 2016)
This thesis examines ownership of the firm by its employees, of varying stakes. It begins by identifying the existence of employee ownership in a Chinese context, presented in the form of a general analytical discussion which is informed by a review of the available evidence on the subject. This work sets the stage for a focus on this form of ownership at the individual level of analysis, involving both conceptual and empirical explorations. Together, this constitutes three papers, put together with introductory and concluding chapters. The first thesis paper identifies the drivers of, and barriers to, employee ownership in China at three levels of analysis: the societal, organisational and individual. Its intended contribution to the employee ownership literature is to organise the scattered evidence in order to provide a systematic and comprehensive coverage of the development of this phenomenon. Employee ownership is found to have played a role in Chinese economic transition as a transitory phase before non-state enterprises were afforded official recognition in a context of publicly-owned enterprise privatisation. Senior managers became the key beneficiaries in firm sales and most ventures that were at one stage employee-owned, dissolved. Outside of a couple of notable examples in the tertiary sector, enterprises featuring some level of employees as owners persist in reduced numbers in rural areas today. In the second thesis paper, the interest is in the role of the individual actor with regard to employee ownership outside of a narrower Chinese context. At this level of analysis, it is preferences (attitudes) and resources which are decisive. A more detailed exploration of the former in particular follows, the idea being to theorise the compatibility of defined individual `types' with specific ownership structures. Yet, because the existence of different forms and mechanisms with regard to employee ownership is not always made clear in the related literature, notable pathways to ownership— cooperative, professional partnership, controlling ownership, share ownership plan mechanism, share option mechanism, and direct ownership—are first clarified to facilitate the analysis. The paper's overall contribution to the literature is the provision of a coherent conceptual treatment of the individual-level antecedents to employee ownership. The third thesis paper comprises mixed-method empirical research into the characteristics of individuals who have recently purchased shares in their employing firms in an Icelandic context, as well as their specific motives for doing so (or reasons for not doing so). Determinants of employee ownership, as well as direct insights into the considerations surrounding share acquisition, are less common at this level of analysis and this is the where the paper contributes to the literature. In order to conduct the empirical analysis, original material is gathered from six case study firms, the details of which are presented within the paper. Income, tenure and age are found to influence ownership status. Furthermore, some support is found for financial motives outweighing non-financial motives behind share purchases in minority employee-owned firms relative to majority employee-owned firms. Internal barriers to ownership, together with a lack of funds, hindered share purchases in majority employee-owned firms in particular.
hdl:10398/9392
Keywords: 650